Logging intensity alters tree species composition and wood density, but not tree diversity, in lowland forests in Vietnam - Suzanne M. Stas; Ervan Rutishauser; Tue Van Ha; Tinh Cong Le; Hieu Dang Tran; Trai Trong Le; Benedict D. Spracklen; Douglas Sheil; Marijke van Kuijk; Oliver L. Phillips; Dominick V. Spracklen (Biodiversity and Conservation, 2026)
Tropical forests host considerable biodiversity but face degradation from timber extraction (“logging”). We examined how logging intensity affected tree diversity, species composition, community wood density and availability of timber species in a lowland forest in north-central Vietnam. We measured and identified trees in 18 quarter-hectare plots that vary in historical logging intensity. Tree diversity showed no significant relationships with logging intensity. However, species composition differed, with each logging intensity class having distinct abundant tree species. Community wood density decreased significantly with logging intensity, being 9% lower in heavily than in lightly logged forests. Timber species were scarce overall, and individuals of harvestable size were most common in lightly logged forests. These results show that while tree diversity can persist after logging, heavy logging shifts community composition towards lighter-wood species and depletes valuable timber trees, reducing both carbon storage and timber potential. Reducing logging intensities is therefore critical for maintaining and increasing community wood density, carbon stocks and sustainable timber supplies in these forests in north-central Vietnam.